The importance of domestic political institutions: Why and how Belgium and Italy qualified for EMU - Mark Hallerberg (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2000)
Why and how did the two European Union countries with the worst debt levels and with yearly deficit levels double the Maastricht target in 1993 manage to get their financial affairs in shape to qualify for Economic and Monetary Union? This paper presents an explicitly institutional approach to the political economy of budget deficits. It discusses the role of one external actor, the European Union, in promoting tighter fiscal discipline in the two countries. The European Union provided an important stick for any failure not to make needed changes, namely exclusion from EMU. This stick alone, however, was not sufficient to promote change in both countries. Indeed, each state made fundamental institutional changes that put the fulfillment of the Maastricht criteria within reach. Consistent with their respective electoral systems and coalition structures, Italy delegated significant power on the making and the enforcement of the budget to a strong finance minister, while Belgium strengthened its High Council of Finance and resorted to budgetary targets in the form of fiscal contracts.
Keywords: 330; Haushaltskonsolidierung; Finanzpolitik; Institutioneller Wandel; Europäische Wirtschafts- und Währungsunion; Konvergenzkriterien